2013
DOI: 10.1371/journal.pone.0066434
|View full text |Cite
|
Sign up to set email alerts
|

BMP7 Gene Transfer via Gold Nanoparticles into Stroma Inhibits Corneal Fibrosis In Vivo

Abstract: This study examined the effects of BMP7 gene transfer on corneal wound healing and fibrosis inhibition in vivo using a rabbit model. Corneal haze in rabbits was produced with the excimer laser performing -9 diopters photorefractive keratectomy. BMP7 gene was introduced into rabbit keratocytes by polyethylimine-conjugated gold nanoparticles (PEI2-GNPs) transfection solution single 5-minute topical application on the eye. Corneal haze and ocular health in live animals was gauged with stereo- and slit-lamp biomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 48 publications
3
101
1
Order By: Relevance
“…Recently, it was suggested that this long challenging problem could be overcome with the use of nano-based drug carriers56. Several recent reports of successful intraocular drugs or gene deliveries by various nanoparticles further increased such expectations18192021222324. The major advantage of nanoparticles is enhanced cellular uptake due to their small size.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that this long challenging problem could be overcome with the use of nano-based drug carriers56. Several recent reports of successful intraocular drugs or gene deliveries by various nanoparticles further increased such expectations18192021222324. The major advantage of nanoparticles is enhanced cellular uptake due to their small size.…”
Section: Discussionmentioning
confidence: 99%
“…Haze scoring was performed according to the Fantes grading scale [29, 30]. Briefly, grade 0 was a completely clear cornea; grade 0.5 had trace haze visualized with careful tangential illumination on slit-lamp biomicroscopy; grade 1 was more prominent haze not interfering with the visibility of fine iris details; grade 2 represented sufficient haze as to cause mild obscuration of iris details; grade 3 was moderate obscuration of the iris and lens; and grade 4 was complete opacification of the cornea in the area of ablation.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the rabbit cornea is being used to study gene transfer procedures (Mohan et al, 2013). A recent study showed that gold nanoparticles coated with BMP7 can reduce corneal fibrosis in the rabbit (Tandon et al, 2013). Disadvantages of using rabbits include higher cost for purchase and maintenance than rats, restricted availability of polyclonal antibodies against various proteins of interest, and reduced availability of genetically diverse strains and transgenic animals.…”
Section: Ex Vivo Experimental Optionsmentioning
confidence: 99%